Subsoil use rights and their social significance. (Journal of actual problems of jurisprudence, 2016)
This article is devoted to social purpose of law. Provides guarantees of the right of the welfare state to uphold the rights and freedoms of man and citizen rights and compliance with the Kazakhstan Subsoil these criteria. In order to improve the legislation of the Republic of Kazakhstan on subsoil for the future is invited to consider the positive experience of legal regulation of subsoil use in developed countries for the possibility of its application in our country.
Keywords: law on mineral resources; social state of law and human sobody subsoil users